Ferromagnetic and Ferroelectric Transformers (Global Journal of Science Frontier Research, 2019)
Physics of the work of transformer with the ferromagnetic core is examined. The new types of transformers with the ferroelectric cores are proposed, and physics of the work of such transformers is also examined.
Keywords: transformer; ferromagnetic material; ferroelectric; inductance